Hedonic Shopping Value dan Shopping Lifestyle Sebagai Determinan Impulse Buying Melalui Positive Emotion pada Generasi Z Pengguna Tiktok Shop - Putri Afiandian; Panji Ulum; Tarjo Tarjo; Widya Pratiwi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of Hedonic Shopping Value and Shopping Lifestyle on Impulse Buying with Positive Emotion as a mediating variable in Generation Z TikTok Shop users in Muara Bungo City. This study uses a quantitative approach with a causal associative method. Primary data were obtained through distributing online questionnaires to 170 respondents selected using accidental sampling techniques. Data analysis was carried out by validity and reliability tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²) analysis using the SPSS version 26 program. The results showed that Hedonic Shopping Value, Shopping Lifestyle, and Positive Emotion had a positive and significant effect on Impulse Buying, both partially and simultaneously. The coefficient of determination (R²) value of 0.732 indicates that 73.2% of the variation in impulsive buying behavior can be explained by these three variables, while the rest is influenced by other factors outside the research model. Positive Emotion has been shown to act as a mediating variable, strengthening the influence of Hedonic Shopping Value and Shopping Lifestyle on Impulse Buying. This finding underscores the importance of emotional aspects and digital lifestyle in driving Generation Z's consumer behavior in the social commerce era.